Recent Advances in the Synthesis and Applications of Phenylquinoline-4-carboxylic Acid Derivatives: A Comprehensive Review - Saha, Sunam; Pathak, Devender; Shah, Kamal (Current Organic Chemistry, 2024)
Phenylquinoline-4-carboxylic acid derivatives have garnered significant attention in recent years due to their diverse pharmacological and industrial applications. This comprehensive review summarizes the latest advancements in the synthesis and diverse range of applications of phenylquinoline-4-carboxylic acid derivatives. This review provides a brief overview of the significance of phenylquinoline-4-carboxylic acid derivatives in medicinal chemistry. It also explores the structural diversity achievable through modifications at various positions of the phenylquinoline-4-carboxylic acid scaffold. The pharmacological applications of phenylquinoline-4-carboxylic acid derivatives, such as anticancer, antimicrobial, anti-inflammatory, and antiviral activities, are highlighted, underscoring their potential as promising drug candidates. This comprehensive review provides a thorough overview of the recent advances in the synthesis and applications of phenylquinoline-4-carboxylic acid derivatives. The integration of synthetic methodologies, structural modifications and diverse applications makes this review a valuable resource for researchers, scientists and professionals working in the fields of medicinal chemistry.
Keywords: anti-malarial